PERANCANGAN SISTEM INFORMASI TAMBAT LABUH KAPAL DI PELABUHAN PERIKANAN NUSANTARA KARANGANTU - Miftahul Farih; Masum Masum; Indra Gunawan; Huswatun Hasanah (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
The purpose of this study is to make it easier to access data and make reports needed by those who need it. The method used in this study is the waterfall model, which begins with research on the current system, design, coding, and maintenance of archive management systems so that archive management information and archive management reports can run quickly, precisely and accurately. The results obtained from this study are regarding the design of a mooring information system that is integrated with a database to support the process of managing ship arrivals and departures easily, quickly, and accurately. In making a ship's arrival and departure certificate, it can be documented into a database, so that it can make it easier if you want to report ship arrival and departure data. The conclusion that can be drawn from this information system is that archive management can be well documented because it is equipped with a database, storage has become a single unit, can reduce redundancy or duplicate data, can display required mooring management information so that it can facilitate officers in making arrival management reports. and ship departure.